Pendidikan Islam dan Pencerahan Spiritualitas: Ikhtiar Menjawab Tantangan Posmodernisme - Suparta Suparta (Ulumuna, 2008)
This article elaborates modern phenomena that come into human’s life with their ambiguous face. On one hand, modernity gives human material and biological satisfaction resulted from advances in science and technology. On the other hand, it leads people to the meaningless life, existentially and spiritually. In the post-modern era, Islamic education is aimed to give alternative solutions which can change human life paradigm from material orientation into spiritual orientation because the Islamic education value can be seen from its contents including maintenance of human life development in all aspects, materially, spiritually, intellectually, socially and experimentally. This article emphasizes that Islamic education does not only justify aqly and naqly knowledge development, but also synthesizes the two into one scientific paradigm.